Comparative virology - Maramorosch, Karl (Academic Press, 1971)
Comparative Virology provides an integrated comparison of viruses, based on their chemical and morphological characteristics. These descriptions will not only give the reader a background but also a detailed analysis of the various groups. In some instances the groups are still host related, as in the case of bacteriophages and polyhedral insect viruses. In others, for instance in pox viruses, the group comprises viruses of vertebrates and invertebrates. The hosts of the bacilliform Rhabdovirales range from man and other warm-blooded vertebrates through invertebrate animals to plants. A special chapter is devoted to viruses devoid of protein-a group that is of great interest and that has only recently been recognized. Since there is historical and practical interest in cologie groupings, such as arboviruses and oncogenic viruses, chapters on such groups have also been included.